Inovasi Hair Tonic Kombinasi Daun Cempedak (Artocarpus integer (Thunb.) Merr.) dan Lidah Buaya (Aloe vera) sebagai Penumbuh Rambut: Hair Tonic Innovation Combination of Cempedak Leaves (Artocarpus integer (Thunb.) Merr.) and Aloe Vera (Aloe vera) as Hair Growth - Liranti, Nintra Mahdan; Duma, Melin Sagita; Dewiningtias, Ni Luh Manik Putri; Marijadi, Kania Adistyawati; Sastyarina, Yurika (Jurnal Sains dan Kesehatan, 2025)
Exposure to high-intensity sunlight can cause hair strands to become dry, brittle, and fall out easily. Hair loss is a disorder that can cause hair to fall off the scalp. The content of flavonoid compounds in cempedak leaves is known to help in the hair growth process and has antioxidant properties. A part from cempedak leaves, aloe vera also contains beneficial substances to reduce hair loss  and stimulate hair growth. This research aims to create and determine the evaluation results of the hair tonic preparation formula combining cempedak leaf extract and aloe vera extract and determine the rabbit hair growth activity of the hair tonic preparation combining cempedak leaf extract and aloe vera. This research is experimental, namely by formulating, carrying out physical evaluations, and testing the activity of a hair tonic preparation combined with cempedak leaf extract and aloe vera. The combination of the two ingredients has been proven to produce optimization of the base formula for hair tonic preparations. The best hair tonic formula base is F3, with better hair growth activity results; namely, the average hair length on the 8th day is 5.85 ± 2.37 mm, and the average hair length on the 15th day is 6 .58 ± 2.99 mm, and 21th day is 9,95 ± 1,71 mm. The organoleptic evaluations, pH levels, homogeneity, viscosity levels, and dry time have met the specified requirements. The results obtained show that the hair tonic preparation made has the potential to grow hair. Keywords:          Hair tonic, hair loss, antioxidant, cempedak leaf, aloe vera   Abstrak Kerontokan rambut merupakan suatu gangguan yang dapat menyebabkan rambut terlepas dari kulit kepala. Kandungan senyawa  flavonoid di dalam daun cempedak diketahui dapat membantu dalam proses pertumbuhan  rambut dan bersifat antioksidan. Selain daun cempedak, lidah buaya juga mengandung zat bermanfaat untuk mengurangi kerontokan rambut serta menstimulasi pertumbuhan rambut. Tujuan dari penelitian ini adalah untuk membuat dan mengetahui hasil evaluasi dari formula sediaan hair tonic kombinasi ekstrak daun cempedak dan ekstrak lidah buaya, serta mengetahui aktivitas pertumbuhan rambut kelinci dari sediaan hair tonic kombinasi ekstrak daun cempedak dan lidah buaya. Penelitian ini dilakukan dengan menformulasikan, melakukan evaluasi fisik, dan menguji aktivitas dari sediaan hair tonic kombinasi ekstrak daun cempedak dan lidah buaya. Kombinasi kedua bahan terbukti menghasilkan optimasi basis formula untuk sediaan hair tonic. Optimasi basis formula sediaan hair tonic yang terbaik adalah Formula 3 dengan hasil aktivitas pertumbuhan  rambut yang meningkat dengan rata-rata yaitu pada hari ke-8 yaitu 5,85 ± 2,37 mm,  hari ke-15 yaitu 6,58 ± 2,99 mm, dan hari ke-21 yaitu 9,95 ± 1,71 mm. Evaluasi organoleptik, kadar pH, homogenitas, kadar viskositas, dan waktu kering yang dilakukan sudah memenuhi persyaratan yang telah ditetapkan. Hasil yang didapatkan menunjukan bahwa sediaan hair tonic yang dibuat berpotensi sebagai penumbuh rambut. Kata Kunci:         Hair tonic, rambut rontok, antioksidan, daun cempedak, lidah buaya